KONSEP WALI HAKIM DALAM PEMBARUAN HUKUM KELUARGA ISLAM DI MALAYSIA DAN INDONESIA - Akhmad Fadly Syahputera; Ferdiyan Ferdiyan (Asy-Syari'ah, 2022)
Malaysia and Indonesia have reformed Islamic law by codifying Islamic family law through statutory regulations. However, between the two countries, there are quite striking differences in regulating guardian judges. This research aims to find out the substance and relevance of reforming Islamic marriage law in two countries related to judges' guardians. The study used a qualitative descriptive-analytical method with the application of laws, namely the Islamic Family Law (UUKI) of all states in Malaysia, the Republic of Indonesia Law no. 1 of 1974 concerning Marriage (UUP), and the Compilation of Indonesian Islamic Marriage Law, especially regarding magistrate guardians. The study results show that the guardian of the king or guardian of the judge is officially and legally recognized in UUKI Malaysia and UUP Indonesia. However, Malaysia's UUKI has yet to have any detailed rules regarding technical procedures for the practice of magistrate guardians. In contrast, Indonesia has these rules even though they are in the form of a Regulation of the Minister of Religion (PMA). Regarding magistrate guardians, Malaysia and Indonesia are included in the Intra-Doctrinal Reform group, which tends to still adhere to conventional fiqh law.